New insights into the synergistic influence of voids and interphase characteristics on effective properties of unidirectional composites. (1st January 2021) - Wang, Kui; Lu, Yue; Rao, Yanni; Wei, Ning; Ban, Jing; Peng, Yong; Yao, Song; Ahzi, Said
Highlights: A novel homogenization scheme for porous UFRCs is presented. Synthetic effects of pores, interphase and fibers on UFRCs' properties are evaluated. Direct analytical results are in good agreement with experimental data. Pores location has great impact on UFRCs' transverse and shear moduli. Abstract: Micro-voids are common imperfections generated during manufacturing or prolonged service of composites. The present paper emphasizes on the effect of not only matrix-pores, but also the interphase-defects on the effective stiffness of unidirectional fiber-reinforced composites (UFRCs). To this aim, a hierarchical modeling of porous UFRCs is established, in which an interphase model is incorporated to characterize the linkage among the fiber content, the content and properties of the interphase, as well as the trait of the interphase-pores. An effective and easy-to-implement two-step homogenization scheme, based on Mori-Tanaka method and Huang's bridging method, is developed for the effective properties of such porous UFRCs. Comparison studies against available experimental data are conducted to demonstrate the validity of the proposed model. Afterwards, detailed parametric analyses are performed, and new insights into the effect of pores on UFRCs are provided, which may have important implications in the further manufacturing and defects speculation of composites.